2014
DOI: 10.1080/13691058.2014.964320
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of Ethiopian women after fistula repair: implications on rehabilitation and social reintegration policy and programming

Abstract: Despite growing recognition of the importance of linking obstetric fistula prevention and treatment strategies with rehabilitation and social reintegration programmes, little research and programming has been oriented toward this goal. Using in-depth interviews, this study aimed to examine the experiences of 51 Ethiopian women after fistula repair surgery to identify priority post-repair interventions that could maximise their quality of life. The results showed that the majority of women felt a dramatic sensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(120 citation statements)
references
References 23 publications
8
99
0
Order By: Relevance
“…, Khisa & Nyamongo , Donnelly et al . ). Three studies reported, women lacked the desire or interest in sex due to their fistula experience (Turan et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…, Khisa & Nyamongo , Donnelly et al . ). Three studies reported, women lacked the desire or interest in sex due to their fistula experience (Turan et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Donnelly et al . ). Consequently, these women became economically dependent on family income for sustenance, and their quality of life and reintegration became compromised (Mselle et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Our identification of non‐incontinence‐related persistent symptoms is also not unique; in a qualitative study of women repaired for fistula in Ethiopia, Donnelley et al . reported that 40% of women reported physical health problems following surgery irrespective of their repair status. The substantial and significant differences in level of reintegration comparing women with persistent physical symptoms and those without support additional intervention to resolve physical symptoms in order to support women's recovery or more targeted psychosocial support and reintegration services to ensure that those coping with physical or psychosocial challenges are appropriately supported.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, 2% of women aged 15-49 years have had fistula, mainly due to obstructed labour (UBOS, and ICF International Inc 2012). Fistula is known to affect the lives of both the woman and her social networks including relatives, especially the husband (Donnelly et al 2015;Women's Dignity Project, Engender Health's 2006). Women with fistula experience multiple losses and are often abandoned by their husbands, who then remarry women who can fulfil marital roles (Mselle et al 2011).…”
Section: Introductionmentioning
confidence: 99%